2013
DOI: 10.5338/kjea.2013.32.3.179
|View full text |Cite
|
Sign up to set email alerts
|

New Estimates of CH<sub>4</sub> Emission Scaling Factors by Amount of Rice Straw Applied from Korea Paddy Fields

Abstract: BACKGROUND: Accurate estimates of total direct CH 4 emissions from croplands on a country scale are important for global budgets of anthropogenic sources of CH 4 emissions and for the development of effective mitigation strategies. Methane production resulted by the anaerobic decomposition of organic compounds where CO 2 acts as inorganic electron acceptor. This process could be affected by the addition of rice straw, water management and rice variety itself. METHODS AND RESULTS: Rice (Oryza sativa L. Japonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…The reduction of greenhouse gas (GHG) emissions is a crucial current issue for most environmental science experts. A major source of GHG emissions are in fact paddy fields (Ma et al ., ; Hadi et al ., ; Kim et al ., ; Ju et al ., ; Suryavanshi et al ., ). A recent report by Jain et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reduction of greenhouse gas (GHG) emissions is a crucial current issue for most environmental science experts. A major source of GHG emissions are in fact paddy fields (Ma et al ., ; Hadi et al ., ; Kim et al ., ; Ju et al ., ; Suryavanshi et al ., ). A recent report by Jain et al .…”
Section: Introductionmentioning
confidence: 97%
“…The reduction of greenhouse gas (GHG) emissions is a crucial current issue for most environmental science experts. A major source of GHG emissions are in fact paddy fields (Ma et al, 2008;Hadi et al, 2010;Kim et al, 2012;Ju et al, 2013;Suryavanshi et al, 2013). A recent report by Jain et al (2013) revealed that in terms of the global warming potential (GWP), SRI could reduce GHG emissions by 28% compared with conventional practice.…”
Section: Introductionmentioning
confidence: 99%
“…논 토양에서 생성된 메탄은 벼 식물체의 통기 조직을 통한 운송, 토양 표층을 통한 불규칙적 분출, 그리고 대기와의 농도 차이에 의한 확산을 주요 경로로 대기로 방출된다 (Gwon et al, 2022). 주요 세 가지 경로 중 논에서 방출되는 메탄의 90% 이상이 벼의 통기 조 직을 통해 대기로 방출되는 것으로 알려져 있어 (NAAS, 2013), 대부분의 연구에서는 이를 주요하게 고려한다 (Seo et al, 2011;Ju et al, 2013;Kim et al, 2016;Jeong et al, 2018). 비록, 논에서 메탄 플럭스를 측정할 때 벼와 함께 토양 표면도 일정 면적 포함되지만, 토양에서 분출과 확산 등을 통해 직접 방출되는 메탄에 대한 연구는 부족하다 (Tokida et al, 2013).…”
Section: Introductionunclassified